Czarny szal : i inne opowiadania - Pirandello, Luigi, 1867-1936.; Pirandello, Luigi, 1867-1936. (Warszawa : Ludowa Spoldzielnia Wydawnicza, 1989)
Polish translations of a selection of short stories by the well-known Italian dramatist.